2020
DOI: 10.1080/0886022x.2020.1726386
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral anastomosis with a polyimide stent in rat kidney transplantation

Abstract: Background: Complications associated with ureteral anastomosis in kidney transplantation are highly prevalent, despite the development of various types of stents. The current stent materials and placement methods have several limitations. This study attempts to provide an alternative by investigating ureteral anastomosis with a polyimide stent and a modified placement method in a rat model of kidney transplantation. Methods: Sprague-Dawley rats were randomly divided into Group I: sham operation, Group II: auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We recommend the placement of a ureteral stent regardless of the surgical procedure, which is beneficial to the recovery of the ureteral anastomosis. Some studies have shown that the placement of a stent through the ureteral-vesical anastomosis is an independent protective factor against ureteral complications after kidney transplantation [ 24 , 25 ]. Open surgery mainly has the problems of unclear anatomical layers, severe tissue adhesion, large trauma, much bleeding, and long operation time, especially for patients with a long time after transplantation and a history of infection, which may result in the failure of the operation due to the fact that the transplant kidney and ureter cannot be accurately located and separated, or the ureter is damaged or the length of the ureter is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend the placement of a ureteral stent regardless of the surgical procedure, which is beneficial to the recovery of the ureteral anastomosis. Some studies have shown that the placement of a stent through the ureteral-vesical anastomosis is an independent protective factor against ureteral complications after kidney transplantation [ 24 , 25 ]. Open surgery mainly has the problems of unclear anatomical layers, severe tissue adhesion, large trauma, much bleeding, and long operation time, especially for patients with a long time after transplantation and a history of infection, which may result in the failure of the operation due to the fact that the transplant kidney and ureter cannot be accurately located and separated, or the ureter is damaged or the length of the ureter is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 55 Microdialysis is a potential alternative to arteriovenous sampling, but has not yet been validated for this purpose. Ureterostomy 56 allows for selective functional monitoring of the injured kidney. The model critically relies on optimized ischemia times in order to achieve actual IR injury and avoid excess incidences of IR damage or non‐function.…”
Section: Discussionmentioning
confidence: 99%
“…These animals are often chosen for the validation of both urethral and ureteral stents. Ureteral stents are inserted through a cystotomy in either the bladder or the ureter [51,55,56]. Besides the evaluation of the device's performance, when placed in the ureter, ureteroureteral anastomosis may also be performed for the histological analysis of ureteral healing and scarring processes [13,55,56].…”
Section: Rat Modelmentioning
confidence: 99%
“…Ureteral stents are inserted through a cystotomy in either the bladder or the ureter [51,55,56]. Besides the evaluation of the device's performance, when placed in the ureter, ureteroureteral anastomosis may also be performed for the histological analysis of ureteral healing and scarring processes [13,55,56]. Urethral stents are tested in the bladder and the urethra, and depending on stent size and characteristics, transurethral placement may be feasible [57][58][59].…”
Section: Rat Modelmentioning
confidence: 99%